Village Fund Allocation Management Competency in Kapala Pitu District, North Toraja Regency - Risma Niswaty; Andi Cudai Nur; Diaz Rency Sesa (Program Pascasarjana Universitas Negeri Makassar, 2021)
This study aims to determine and describe the Competence of Village Fund Allocation Management in Kapala Pitu District, North Toraja Regency. The method used is an interactive model, namely data collection, data condensation, data presentation, and verification of conclusions. The results show that 1) The availability of adequate information about village funds is considered to have been implemented effectively. 2). Public knowledge and insights about village funds are considered to have been implemented effectively. 3). Increasing public trust in the management of the Village Fund is considered to have run effectively. 4). The increased community participation in village fund activities is considered to have been implemented effectively. Overall, it can be understood that the Competency of Village Fund Allocation Management in Kapala Pitu District, North Toraja Regency has been running effectively. project finished. So that the responsiveness of the village community in Kapala Pitu to the implementation of village governance runs well, the allocation in the implementation of the village fund program has been able to increase public trust in the village government, the result is that village development is getting more advanced. The creation of a good relationship between the community and the government through community empowerment with the labor-intensive model of the local village community is given the opportunity to implement the village fund program both in physical and non-physical development.